OP0352 An increased prevalence of periodontal disease, porphyromonas gingivalis and aggregatibacter actinomycetemcomitans in anti-ccp positive individuals at-risk of inflammatory arthritis. (12th June 2018) - Mankia, K.; Cheng, Z.; Do, T.; Kang, J.; Hunt, L.; Meade, J.; Clerehugh, V.; Speirs, A.; Tugnait, A.; Hensor, E.; Devine, D.; Emery, P.
Abstract : Background: The prevalence of periodontal disease is increased in RA, and periodontitis is associated with the bacterium Porphyromonas gingivalis (Pg), which can citrullinate arginine residues. 1 These observations suggest periodontitis may be a key initiator of RA-related autoimmunity. Importantly, clinical periodontal disease, and the relative abundance of periodontal bacteria have not been described in seropositive individuals at risk of developing RA who do not have synovitis. Objectives: To investigate the prevalence of periodontal disease and the relative abundance of key periodontal bacteria in anti-CCP positive at-risk individuals without synovitis. Methods: Anti-CCP positive individuals with musculoskeletal symptoms but no clinical synovitis (CCP+), early RA (RA) patients and healthy controls (HC) were recruited. CCP +underwent a 38 joint ultrasound (US) assessment. Periodontal examination was performed by a dentist; six sites per tooth were assessed for clinical attachment level (CAL), pocket depth (PD) and bleeding on probing (BOP). Periodontal disease sites (PDD) were defined as CAL≥2 mm and PD ≥4 mm. A clinical consensus was agreed for each case by three dentists. DNA, isolated from subgingival plaque from diseased and healthy periodontal sites, was pair-end sequenced (Illumina HiSeq3000). Taxonomic and functional profiles were obtained from MG-Rast and differences between groups studied using DESeq2. Mann-Whitney U tests were used to compare groups and Spearman Rho used for correlations. For metagenomic data, Wald test was used to compare relative abundance. Results: 48 CCP+, 26 RA and 32 HC were recruited. Groups were balanced for age, sex and smoking. All but 2 (96%) CCP +had no US synovitis (greyscale ≥1 and power Doppler≥1). Dentists classified 73% CCP+, 38% HC (p=0.02) and 54% RA as having clinical periodontitis. The percentage of periodontal sites with CAL ≥2 mm, PD ≥4 mm, BOP, PDD and active PDD (PDD +BOP) were all greater in CCP +compared to HC (p<0.05) and similar to RA. In non-smokers, PDD and active PDD were more prevalent in CCP +compared to HC. Metagenomic data indicated CCP +had increased relative abundance of both Pg and Aggregatibacter actinomycetemcomitans ( Aa ) compared to HC (p<0.001) and RA (p<0.01). However, clinical periodontitis was only associated with increased relative abundance of Pg (p<0.001) but not Aa. Furthermore, the relative abundance of Pg was associated with the percentage of sites with active PDD in CCP+ (p=0.05) and HC (p=0.04) but this was not seen for Aa (figure 1). Conclusions: We report an increased prevalence of periodontal disease, Pg and Aa in anti-CCP positive at-risk individuals without synovitis. Interestingly, relative abundance of Pg, but not Aa, was associated with periodontitis, suggesting potential mechanistic differences that require further exploration. These data support the concept that periodontal inflammation and periodontopathic bacteria may both be important in the initiation of RA-related autoimmunity. Reference: [1] Lundberg K. Nat Rev Rheumatol2010. Disclosure of Interest: None declared